2015
DOI: 10.1002/ps.4064
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of Magnolia denudata seed hydrodistillate constituents and related compounds and liquid formulations towards two susceptible and two wild mosquito species

Abstract: Reasonable mosquito control in the aquatic environment can be achieved by MD-SHD 50 mg L(-1) liquid as a potential larvicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
1
23
0
2
Order By: Relevance
“…Limonene is a chiral molecule. We have screened the enantiomer R‐(+)‐limonene for larvicidal activity and confirmed the earlier reporter's observation that limonene has good mosquito larvicidal potential (Pavela, , ; Santos et al, ; Wang et al, ). Additionally, the insecticidal activity of EOs containing limonene as one of the active ingredients have been reported (Govindarajan et al, ; Pavela, ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Limonene is a chiral molecule. We have screened the enantiomer R‐(+)‐limonene for larvicidal activity and confirmed the earlier reporter's observation that limonene has good mosquito larvicidal potential (Pavela, , ; Santos et al, ; Wang et al, ). Additionally, the insecticidal activity of EOs containing limonene as one of the active ingredients have been reported (Govindarajan et al, ; Pavela, ).…”
Section: Discussionsupporting
confidence: 83%
“…Our study has showed better larvicidal activity (LC 50 9.76 ppm) against Ae. aegypti larvae than most of the earlier reports by the researchers on the larvicidal potency of γ‐terpinene (Cheng et al, ; Santos et al, ; Wang et al, ) except the report by Lucia et al (). The EOs showing insecticidal activity where γ‐terpinene as one of the chemical constituents has also been reported earlier (Pavela, ; Sutthanont et al, ).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Las plantas han aprovechado a los insectos como agentes polinizadores, pero también han tenido que desarrollar mecanismos de defensa contra insectos depredadores (21). En este contexto, los aceites esenciales y sus componentes se destacan como compuestos potencialmente útiles contra los insectos (22,23).…”
unclassified